(untitled) (Texas Journal of Engineering and Technology, 2026)
In this article, we conducted research on the safety of ultrasound equipment using the FMEA method. The work performed in this study was carried out in accordance with the requirements of the international standard “IEC 60601-2-37:2024 Particular requirements for the basic safety and essential performance of ultrasound medical diagnostic and monitoring equipment” and “ISO 14971:2019 (E) Medical devices - Application of risk management for medical devices”. The study was conducted at the “YYY” diagnostic center in Andijan. The study is based on the results obtained from 150 patients over a three-month observation period. During the study, the initial average RPN level was 175.8, and due to corrective measures, it was reduced by 44.7, or 74%. The work in the study is part of the results of my scientific research on the topic “Improvement of the quality assurance system for ultrasound examinations in medicine based on international standard requirements”